Pengaruh Intellectual Capital, Capital Structure terhadap Firm Performance dengan Moderasi Corporate Governance - Viriany, Daniel, (Fakultas Ekonom dan Bisnis, Universitas Tarumanagara, 2021)
The purpose of this research is to analyze the impact of intellectual capital and capital structure as independent variable on firm performance as dependent variable with the role of corporate governance as moderating variable. This research use purposive sampling as sampling method. This research was conducted on manufacturing companies listed on IDX during 2018 to 2020 with selected 82 manufacturing companies and total observation of 225 samples. This research uses multiple regression analysis with Random Effect Model (REM) as regression model. The results before interaction showed that intellectual capital had a significant positive effect on firm performance. Capital structure has a significant negative effect on firm performance. After interacting with moderating variables, the results showed that corporate governance didn’t succeed moderating the influence of intellectual capital and capital structure on firm performance.